The Impact of Nursing Rounds and Pre–Post Conferences on Nursing Care Quality: A Literature Review - Luisa da Costa Belo; Dyah Wiji Puspita Sari; Muhammad Abdurrouf; Iwan Ardian (GLOBAL HEALTH SCIENCE GROUP, 2026)
The quality of nursing services is a critical determinant of patient safety, care effectiveness, and overall patient satisfaction. Nursing rounds and pre–post conferences are widely implemented strategies to enhance team coordination, clarify care plans, and improve the quality of nursing care delivery. This study aimed to systematically review the impact of nursing rounds and pre–post conferences on nursing care quality outcomes. A systematic literature review was conducted in accordance with the PRISMA 2020 guidelines. Electronic searches were performed in PubMed, ScienceDirect, Scopus, ProQuest, and Google Scholar for studies published between 2020 and 2025 using relevant MeSH terms and keywords related to nursing rounds, pre–post conferences, and nursing care quality. The review process involved identification, screening, eligibility assessment, and inclusion of studies. Original studies and systematic reviews conducted in nursing settings that reported quality-related outcomes were included. Case reports, editorials, conference abstracts without full text, and studies without a clear description of the intervention were excluded. Of the 312 records identified, 12 studies met the inclusion criteria. The findings indicate that nursing rounds and pre–post conferences were associated with improvements in patient satisfaction, quality of nursing documentation, patient safety outcomes, and work efficiency, although the magnitude of effects varied across settings and study designs. Nursing rounds and pre–post conferences have a positive impact on multiple dimensions of nursing care quality and represent effective strategies for enhancing nursing service delivery.